Designing the Integration of Science in Madrasas - Suradi, Suradi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The goal of this research is to determine how far the process of integrating knowledge in madrasas has progressed, as well as to provide solutions to maximize knowledge integration in madrasas. The author conducts library research using a qualitative descriptive approach, which consists of collecting books related to the object of research or research that is library in nature. According to the findings of research on the integration of science in madrasas, there are at least three priority issues that must be addressed by madrasas in order for the integration of science to achieve ideal results. Curriculum, teaching staff, and learning resources are three examples.